GREEK COASTAL MIRES: A PRELIMINARY STUDY OF THE AGOULINITSA PEATLAND, WESTERN PELOPONNESE - Sofikitis, E.; Siavalas, G.; Chatziapostolou, A.; Kalaitzidis, S.; Christanis, K. (Bulletin of the Geological Society of Greece, 2007)
The Agoulinitsa peatland formed on the western shore of the homonymous lake, which was drained in 1969 because of the emerging demand for agricultural land. This study is a preliminary attempt to determine the conditions that prevailed during peat formation. Shallow cores were obtained from the peatland and initial physical, chemical and mineralogical analyses were carried out. High ash yield and pH values indicate that peat accumulated under alkaline conditions with periods of high clastic material influx, while high electric conductivity values indicate increased influx of dissolved solids into the mire. The mineral matter consists mainly of clay minerals, quartz, calcite, halite, sylvite and pyrite. The distribution of these minerals with depth indicates that fresh-water conditions prevailed for a long period during peat accumulation at the central part of the peatland, whereas the sea-water influence was more intense to the south establishing slightly brackish conditions. All data suggest that the Agoulinitsa peatland was developed as a back-barrier mire formed at the southwestern part of the Agoulinitsa Lake, and hence it can be considered as a modern analogue of the Neogene lignite deposits occurring along the west coast of Péloponnèse